Fifty contemporary choreographers - Butterworth, Jo; Sanders, Lorna (Routledge key guides, 2020)
"Fifty Contemporary Choreographers is a unique and authoritative guide to the lives and work of prominent living contemporary choreographers; this third edition includes many new names in the field of choreography. Representing a wide range of dance genres and styles, each entry locates the individual in the context of contemporary dance and explores their impact. Those studied include: Kyle Abraham Germaine Acogny William Forsythe Marco Goeke Akram Khan Wayne McGregor Crystal Pite Frances Rings Hofesh Shechter Sasha Waltz With an updated introduction by Deborah Jowitt and further reading and references throughout, this text is an invaluable resource for all students and critics of dance and all those interested in the ever-changing world and variety of contemporary choreography"--